PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H.; Meigs, Walter B. (The Accounting Review, 1959)
Featured here are problems that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the first half of the CPA examination in accounting practice on May 13, 1959. Examination pattern involves the division of the whole duration of the paper among three divisions. The first division of questions involve objective type of questions aimed at measuring the skills of the examinee related to federal income taxes under the U.S. Internal Revenue Code, 1954. The second division is aimed to test the examinees skills in the maintenance of check book and cash book of a law firm whose owners have decided to dissolve their partnership. Information regarding capital investments, profits and expenditures have been provided. Another question requires the examinee to calculate inventory costs transferred from different product lines; for a company manufacturing different industrial products. Questions demanding the preparation of a balance sheet and working capital fund are also presented.